A multiplicidade pela sintaxe cinematográfica: uma análise dos filmes Smoking e No smoking de Alain Resnais - Santos, Cesar Augusto Baio (2006)
The object of study of this research is the multiplicity at the semiotic process in Smoking and No Smoking, aiming to deep in the narrative and esthetics questions of these Alain Resnais movies. At the same time they structure themselves on a new way of narrative, these two twin works point out to the dissolution of the esthetics barriers determined by the formats, incorporating to them different languages, esthetics, genres and works. The movies come from the same situation to develop twelve different and independent stories, carnivaling the characters sense, sequence and dialogs. To this narrative complexity, add esthetics elements from the XIX century scenery to the games, from the theater to the hipertextual applicative. This diversity of elements points out to a multiplicity produced at the building of sense in the narrative and esthetics sphere. The notion of multiplicity is assumed at the same time as being an integrant of the object of study and of the analysis methodology carried out. In this sense, the multiplicity concept suggested by Ítalo Calvino is taken into account, on the literature field, in the search of a theoretical deep at the contemporary thinking. This way is made possible through Mikhail Bakhtin s concepts of polyphony, dialogism and carnivalesque and to Gilles Deluze and Feliz Guattari s notions of rhizome, moving forward to the dialogic relations among movie, theater, scenery, digital means, information architecture and games. Finally, the approach between the multiplicity applied in Smoking and No Smoking and the concept of rhizome is carried out, making evident that multiplicity is essential in the building of sense process at Resnais works